Persepsi Siswa Tentang Eksistensi Museum Sang Nila Utama Dalam Pembelajaran Sejarah Di Smk Negeri 2 Pekanbaru - Bonita Padang; Isjoni Isjoni; Yuliantoro Yuliantoro (Peneliti.net, 2023)
This study aims (1) to determine the conditions of history learning at SMK Negeri 2 in terms of the sources used. (2) To find out the existence of the Sang Nila Utama Museum in supporting student history learning at SMK Negeri 2 Pekanbaru. (3) To find out students' perceptions about the existence of the Sang Nila Utama Museum in history learning at SMK Negeri 2 Pekanbaru. Data were collected through observation, interviews and documentation studies. In this study the authors used data analysis techniques provided by Miles and Huberman, namely 3 components of analysis, namely data reduction, data presentation and drawing conclusions and verification. History learning at Vocational High School (SMK) Negeri 2 Pekanbaru is going well and effectively. The Sang Nila Utama Museum can be a very useful source of history learning for students at school. The results of this study concluded that the perceptions of students at SMK Negeri 2 Pekanbaru about the existence of the Sang Nila Utama Museum are known to mean that students have positive perceptions which means they are quite good. Students argue that the existence of the Sang Nila Utama museum makes learning history more interactive and not boring.